Diferentes formas de utilização do QDF ao longo ciclo de desenvolvimento do produto - Flavio de Aguiar Araujo (2002)
This dissertation presents a study, conducted in the last three years, about different forms of QFD use, during product development cycle. The study was conducted in three Brazilian companies, two of the automobile industry (an European automobile assembly subsidiary plant and a national capital auto-supplier manufacturer), the third one a mobile Internet technology company which is based in software development. Quality Function Deployment (QFD) emerged in the beginning of 1970 and have been being continuously improved during the last three decades, culminating in the full model, described by OFUGI. However, sometimes is not possible to use the method in it's entire potential, being necessary to use it with some flexibility, due to a series of factors, such as: context in which the company is inserted, type of product, team domain of the method, company products development process contingencies, product development phases involved in the project, and others. The main objective of this dissertation is to demonstrate how QFD method can be used with some flexibility in different situations during the product development cycle. To reach this main objective same specifics are proposed: (1) to describe the QFD use to guarantee conformity quality, focused only in the try out phase of a new engine line, identifying the benefits and limitations of it's use ; (1) to describe QFD use, identifying it's benefits and limitations, to help the co-design of a automotive component in an auto-supplier manufacturer, combined with mechanical design techniques such as finite elements methods and others ; (3) to describe the QFD use in a derivative product development process, based on an existing platform of a mobile Internet technology company, identifying it's benefits and limitations ; (4) to describe the use of QFD in a new platform product development, in a mobile Internet company, identifying it's benefits and limitations; (5) to identify the similarities and differences in the method applications on these different presented situations. To reach these objectives the Action-Research methodology was used in four interventions conducted in the three companies referred. The main conclusion of this work is the necessity of a bigger flexibility and creativity in the QFD application method due to the variations that can be found in the product development process. These variations are caused by variables like sector context, organizational company structure, product characteristics, process characteristics, project scope and type of contact between product and user